DIAGNOSING APRAXIA OF SPEECH IN SLOW LEARNING PUPILS - Wissam Sahib Moussa Al-Braqee; Dr. Nawras Shakir Hadi Al -Abbas; Aqeel Khalil Nasser Al-Tufayli (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
This research aimed to identify apraxia of speech for slow learning pupils, and to identify statistically significant differences in apraxia of speech, according to the gender variables (males, females), and grade (second, fourth) for slow-learning pupils. The researcher constructed the scale apraxia of speech after translating the standards set by the American Society for Speech, Language and Hearing into Arabic, and after presenting it to a group of experts, the scale would consist of (34) paragraphs in a final form. Then the researcher applied the scale on an intentionally selected sample, where the research community consisted of slow learning students who suffer from speech and language disorders in the primary schools of the Holy Karbala State Education Directorate, whose number is (n=170) and the number of males and females is (n=106) in the second grade and the number of males and females (n=64) are in fourth grade. The researcher used the descriptive correlational search method in collecting the data. The validity and reliability of the scale were verified and the appropriate statistical means were used, and it was extracted by means of the SPSS data package. The result in Table (1) indicates the existence of a statistically significant difference, as the calculated T value of the apraxia of Speech Scale reached (4,583) degrees, which is greater than the tabular value of (1,960) degrees. The result in Table (2) indicates there is no statistically significant difference in apraxia of speech according to the gender variable, as the calculated mean value was (0.436), which is less than the tabular value (3.84), at a level of significance (0.05) and a degree of freedom (169), and this indicates that the male and female subjects of the research sample had the same level of apraxia of speech. There is a statistically significant difference in apraxia of speech according to the stage variable, as the calculated Fatal value (38.27) was greater than the tabular value (3.84) in favor of the second grade, as the arithmetic mean of their scores reached (79,257) degrees, which is greater than the arithmetic mean For the fourth-grade grades (67,26) marks. The research sample, who are slow learners, had high levels apraxia of speech. The results also indicated that apraxia of speech didn't make a difference in gender (males, females). The results also indicated that the severity apraxia of speech decreased as the student progressed through the other educational stages, due to the accumulation of educational experiences.